2016
DOI: 10.5121/ijci.2016.5208
|View full text |Cite
|
Sign up to set email alerts
|

Overall Performance Evaluation of Engineering Students Using Fuzzy Logic

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…The comparison between classical and fuzzy evaluation indicated that only in thesis 4 there is no difference between two levels of evaluation. More important, 96.15% of master theses obtained higher classical mark, similar to results obtained in Kharola et al (2015), Guruprasad et al (2016) and Surya et al (2016) who found higher classical mark in faculty performance evaluation. The advantage of a fuzzy approach is a possibility of modelling the level of severity of evaluation criteria by changing fuzzy methodology.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The comparison between classical and fuzzy evaluation indicated that only in thesis 4 there is no difference between two levels of evaluation. More important, 96.15% of master theses obtained higher classical mark, similar to results obtained in Kharola et al (2015), Guruprasad et al (2016) and Surya et al (2016) who found higher classical mark in faculty performance evaluation. The advantage of a fuzzy approach is a possibility of modelling the level of severity of evaluation criteria by changing fuzzy methodology.…”
Section: Resultssupporting
confidence: 88%
“…Contemporary studies are also oriented to evaluation of students' performance (Kharola et al, 2015;Surya et al, 2016;Varghese et al, 2017), faculty teachers' work (Pavlović, 2016) and general evaluation practices (Du Prel et al, 2009). It is important to note that main obstacles students are facing with in the process of preparing and writing master theses are the definition of research objectives, the methodology of data analysis and the argumentation of obtained data (results).…”
Section: Introductionmentioning
confidence: 99%
“…Guruprasad et al (2016) obtained higher classical (statistical) value in 90.91% of cases (or 10 out of 11 cases) in faculty performance evaluation. Based on theory, laboratory and project data (Surya et al, 2016) student performance was higher in all nine cases, by using classical methodology.…”
Section: Tab 3 Comparison Between Classical and Defuzzification Marmentioning
confidence: 90%
“…The fuzzy evaluation of teachers' academic performance (Chaudhari et al, 2012) and faculty performance as well is also investigated (Guruprasad, et al, 2016;Jyothi et al, 2014). New studies are still oriented to evaluation of students' performance by a fuzzy logic (Kharola et al, 2015;Surya et al, 2016;Varghese et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…They have obtained better results in evaluation with their fuzzy approach when compared to traditional methods. A.A. Surya et al [9] have proposed a flexible fuzzy evaluation system for student performance in school or college. In their system the membership function deployed can be changed as per the need of time and system.…”
Section: Defuzzificationmentioning
confidence: 99%